Acoustics at the Gdańsk Technical University - SANKIEWICZ, M.; BUDZYŃSKI, G. (Archives of Acoustics, 1993)
History of the development of acoustics at the Gdańsk Technical University within the past half-century is briefly outlined. A contribution of the Gdańsk acousticians to the development of acoustics on the country-wide scale is characterized. A decisive influence of Professor Malecki’s achievements on the growth of the Gdańsk acoustical milieu is demonstrated.